How does the gymnastic apparatus influence the muscle activity of a gymnast in a handstand? - Niespodzinski, B.; Kochanowicz, A.; Mieszkowski, J.; Zasada, M.; Sawczyn, S. (21st Annual Congress of the European College of Sport Science (ECSS), Vienna, 6. -9. July 2016, 2016)
Introduction: Gymnasts perform handstands on various apparatus, both in stable und unstable conditions. Such a balance task requires specific muscle activation which should differ depending on the wrist joint position and the specificity of the apparatus. Therefore, the aim of the study was to show differences in surface electromyography activity (sEMG) of gymnasts` muscles during a handstand on various apparatus. Methods: 10 elite male gymnasts participated in the study. Their mean age was 25 ± 3.94 years. In the study, gymnasts performed a 5-second handstand in three conditions: on the floor, on parallel bars and on still rings. During performance, sEMG of 13 muscles was recorded. Mean values of three proper handstands on each apparatus were taken into analysis. Each value was normalized to maximal voluntary isometric contraction (MVIC) performed on Biodex System 4. Results: In comparison to a handstand on the floor (60 ± 28%), gymnasts` wrist flexors muscles on parallel bars (42 ± 25%) and still rings (43 ± 32%) exhibited decreased mean percentage activity of the MVIC. On parallel bars it was associated with an increase in rectus femoris activity by about 76% in comparison to that on the floor. Most of the muscles (biceps brachii, deltoids, pectoralis major, latissimus dorsi, trapezius descendens) showed increased activity in unstable conditions of still rings. The activity of triceps brachii (15% MVIC) did not differ between each condition. Discussion: The reason for such results may lie in different positions of wrist joints, where on the floor the wrist flexors are the most active muscle group, which determines balance in an inverted position (Hedbávný et al., 2008). Parallel bars enforce a specific hand grip, which shows more balanced sEMG activity of wrist flexors and extensors. As this provides less mobility in the wrist joint due to a lesser range of abduction/adduction motions in it as well as its lower torque production capabilities in such motions (Delp et al., 1996), it may facilitate the use of the two other (shoulder and hip) strategies (Yeadon and Trewartha, 2003), manifested by an increase in the lateral deltoid and the rectus femoris activity. Conclusions The obtained results showed that unstable conditions of still rings increase the sEMG activity of all gymnasts. A different handgrip position between a handstand on the floor and on parallel bars can change the activity of not only forearm muscles but also distal muscles.